Theatre and the law: a dramaturgical analysis of Comcare v PVYW - Ryan Roberts (Law Text Culture, 2021)
The law and theatre are uniquely entwined. The traditionalist notion of the law being an entirely intellectual exercise has, in some ways, limited its application. The law consistently uses techniques that explore knowledge through the use of the body, whether we realise it or not. Within the purview of Gageler J’s dissent in the case Comcare v PVYW, this article sought to explore methods that engage the use of the body to be able to understand, interpret and apply the law. This exploration used a range of dramaturgical techniques to reappraise the case. For example, it examines key legal principles by physically representing them. This included ideas such as precedent and court hierarchy. By doing so, it opened a window to explore the way in which we can understand the law and its relationship to humanness beyond the intellectual. Interestingly, this process produced a number of conclusions. It exposed that the application of dramaturgy to the law can act as a bridge to close the gap between the obscurity of the law and the people that interact with it. As practitioners of the law, sometimes it is easy to forget it’s audience – human beings. It can become so convoluted that it alienates a broad section of its audience but it is through these techniques that we can at least realise this pitfall. This process also challenged the assumptions that are made about the law and, more broadly, it has promoted the importance of legal practitioners to look beyond their own experiences to better understand the holistic effect the law.